Rectal Dose Is the Other Dosimetric Factor in Addition to Small Bowel for Prediction of Acute Diarrhea during Postoperative Whole-Pelvic Intensity-Modulated Radiotherapy in Gynecologic Patients - Huang, Eng-Yen (Cancers (Basel), 2021)
SIMPLE SUMMARY: Although the small bowel volume effect for acute diarrhea during radiotherapy has been investigated, no study has reported the influence of rectal dose. We analyzed 108 patients undergoing intensity-modulated radiotherapy after hysterectomy. Acute diarrhea was defined as onset during radiotherapy based on Common Terminology Criteria for Adverse Events (CTCAE) version 3. Both small bowel and rectum dosimetric parameters affected Grade 2 to 3 diarrhea. The high-dose volume effects on the small bowel still play an important role in postoperative intensity-modulated radiotherapy. This is the first large cohort study to demonstrate the role of both IMRT dosimetric factors of the rectum and the small bowel in acute diarrhea in gynecological patients with a previous hysterectomy. A small bowel volume of 39.6 Gy < 60 mL and a mean rectal dose of <32.75 Gy are suggested as constraints to treatment planning. ABSTRACT: We studied the association of rectal dose with acute diarrhea in patients with gynecologic malignancies undergoing whole-pelvic (WP) intensity-modulated radiotherapy (IMRT). From June 2006 to April 2019, 108 patients with previous hysterectomy who underwent WP IMRT were enrolled in this cohort study. WP irradiation of 39.6–45 Gy/22–25 fractions was initially delivered to the patients. Common Terminology Criteria for Adverse Events (CTCAE) version 3 was used to evaluate acute diarrhea during radiotherapy. Small bowel volume at different levels of isodose curves (Vn%) and mean rectal dose (MRD) were measured for statistical analysis. The multivariate analysis showed that the MRD ≥ 32.75 Gy (p = 0.005) and small bowel volume of 100% prescribed (V100%) ≥ 60 mL (p = 0.008) were independent factors of Grade 2 or higher diarrhea. The cumulative incidence of Grade 2 or higher diarrhea at 39.6 Gy were 70.5%, 42.2%, and 15.0% (p < 0.001) in patients with both high (V100% ≥ 60 mL and MRD ≥ 32.75 Gy), either high, and both low volume-dose factors, respectively. Strict constraints for the rectum/small bowel or image-guided radiotherapy to reduce these doses are suggested.